PRODUCTION AND CHARACTERIZATION OF ANTI-DIABETIC GOLD NANOPARTICLES USING THE LEAF EXTRACT OF MANGIFERA INDICA (FUDMA JOURNAL OF SCIENCES, 2024)
Diabetes has continued to affect the well-being of millions of individuals all over the world. More than seventy percent of Africans have undiagnosed diabetes mellitus, with Nigeria among the list of the African countries recording most undiagnosed cases. Biologically synthesized gold nanoparticles using the extracts of plants have continued to gain grounds in the treatment of diabetes. In the present research, a straightforward green method was used to form gold nanoparticles (AuNPs) from Mangifera indica leaf extract. Transmission electron microscopy (TEM), dynamic light scattering (DLS), ultraviolet visible spectroscopy (UV-Vis), X-ray diffraction (XRD), and selected area electron diffraction (SAED) were used to characterize the nanoparticles. Using XRD and SAED, the AuNPs' crystallinity was ascertained. The TEM revealed particles of various morphologies, and the UV-Vis revealed a surface plasmon resonance (SPR) at 539 nm. The stability of the colloidal suspension was implied by the DLS measurement, which revealed a hydrodynamic size of 31.74 nm and a zeta potential of -23.7 mV. With percentage inhibitions that were about equivalent to that of acarbose, the conventional medication, the AuNPs demonstrated strong antidiabetic efficacy against the alpha-glucosidase and alpha-amylase enzymes. The research revealed the potential of Mangifera indica leaf extract-mediated gold nanoparticles in treatment of diabetes.
Keywords: Green nanotechnology; Mangifera indica extract; Green synthesis; Enzymes